Manifestations of the religious dimension in the 1 November 1954 Declaration: a reading of the document - tahri, fatima (Journal of Social Sciences and Humanities, 2016)
⚠ Clarification Notice: This article was originally published in this journal (2016) and was later republished in another journal without authorization. Editorial clarification The Declaration of 1 November 1954 is considered the most important ideological document among the documents of the Algerian Revolution. It still retains its historical value despite the passage of six decades since its issuance. Although numerous studies have been conducted on it, it remains difficult for a single researcher to encompass all its concepts and provide a comprehensive explanation. Therefore, this article addresses only one aspect among the multiple dimensions contained in the declaration, namely the religious dimension. This foundational document included a set of principles and values which, even if they carry a humanistic or civilizational character, are ultimately derived from the spirit of Islam and its values. They stem from the authenticity and culture of Algerian Muslim society.